Environmental History of the Rhine-Meuse Delta An ecological story on evolving human-environmental relations coping with climate change and sea-level rise - Nienhuis, P.H (Springer Netherlands : Imprint: Springer, 2008)
This book presents the environmental history of the Delta of the lowland rivers Rhine and Meuse, an ecological story on evolving human-environmental relations coping with climate change and sea-level rise. It offers a combination of in-depth ecology and environmental history, dealing with exploitation of land and water, the use of everything nature provided, the development of fisheries and agriculture, changes in biodiversity of higher plants, fish, birds, mammals and invasive exotics. It is the first comprehensive book written in English on the integrated environmental history of the Delta, from prehistoric times up to the present day. It covers the l- acy of human intervention, the inescapable fate of reclaimed, nevertheless subs- ing and sinking polders, 'bathtubs' attacked by numerous floods, reclaimed in the Middle Ages and unwittingly exposed to the rising sea level and the increasing amplitude between high and low water in the rivers. The river channels, constricted and regulated between embankments, lost their flood plains, silted up, degraded and incised. Cultivation of raised bog deposits led to oxidation and compacting of peat and clay, resulting in progressive subsidence and flooding; arable land had to be changed into grassland and wetland. For millennia muscular strength and wind and water powers moulded the country into its basic form. From 1800 onwards, acceleration and scaling up by steam power and electricity, and exponential popu- tion growth, resulted in the erection of human structures 'fixed forever', and severe pressure on the environment.